2017
DOI: 10.1007/s00420-017-1224-0
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to extremely low-frequency magnetic fields and risk for central nervous system disease: an update of a Danish cohort study among utility workers

Abstract: We observed elevated risks of dementia, motor neurone disease, multiple sclerosis and epilepsy and lower risks of Parkinson disease in relation to exposure to ELF-MF in a large cohort of utility employees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 34 publications
0
28
1
Order By: Relevance
“…In this context, extremely low frequency magnetic fields (ELF‐MFs), arising from power lines and electric devices, have been classified as possible carcinogens (2B) by the International Agency for Research on Cancer [IARC, ]. Moreover, ELF‐MF exposure has been associated with an increased risk of neurodegenerative diseases, mainly Alzheimer's Disease (AD) and Amyotrophic Lateral Sclerosis (ALS) [Consales et al, ; Jalilian et al, ; Huss et al, ], and possibly Parkinson's Disease (PD) onset and/or progression [Brouwer et al, ; Huss et al, ; Pedersen et al, ]. We recently demonstrated that exposure to 50 Hz (1 mT) MF triggers a massive redox imbalance in both proliferating and post‐mitotic SH‐SY5Y dopaminergic cells, and sensitizes neuronal cells to the PD neurotoxin MPP + by stimulating oxidative stress, protein carbonylation, and programmed cell death [Benassi et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, extremely low frequency magnetic fields (ELF‐MFs), arising from power lines and electric devices, have been classified as possible carcinogens (2B) by the International Agency for Research on Cancer [IARC, ]. Moreover, ELF‐MF exposure has been associated with an increased risk of neurodegenerative diseases, mainly Alzheimer's Disease (AD) and Amyotrophic Lateral Sclerosis (ALS) [Consales et al, ; Jalilian et al, ; Huss et al, ], and possibly Parkinson's Disease (PD) onset and/or progression [Brouwer et al, ; Huss et al, ; Pedersen et al, ]. We recently demonstrated that exposure to 50 Hz (1 mT) MF triggers a massive redox imbalance in both proliferating and post‐mitotic SH‐SY5Y dopaminergic cells, and sensitizes neuronal cells to the PD neurotoxin MPP + by stimulating oxidative stress, protein carbonylation, and programmed cell death [Benassi et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…This is more than just the Gompertzian hypothesis, people living longer to develop disease they died too young to have in former time, [14][15][16][17] nor is it likely to be just better diagnosis, rather the rapid change and possible interactions of levels of Electromagnetic field backgrounds, heavy metals, spin generating Reactive Oxygen Species, organophosphates and hormone disrupting chemicals in the human environment. 21,[31][32][33]35,36,38,40,47,54 Finally, despite the limitations of the study, we state with the greatest caution that it appears that a head injury and/ or an electric shock might possibly have contributed to the development of MSA as well as occupation and be the tripping point.This hypothesis stimulating pilot study suggeststhat there would be value in a more detailed subsequent exploration of these disproportionate traumatic and occupational factors that might contribute to the development of and increases in Multiple Systematic Atrophy.…”
Section: Discussionmentioning
confidence: 84%
“…Exploring the literature on such events, a link between neurological disease and electric shock was described by Dureux in 1958 43 but the evidence on electric shock and neurological disorders is inconsistent, some report either no association or the linkage is very weak 34,47 whilst others have found a significant connection. 37,38,[50][51][52][53][54][55] A study of particular possible relevance strongly indicated that there appeared to be a degree of delayed neurological reaction, from months to many years, before symptoms appeared. 56 In a systematic review by Campbell & Dini they make a very strong case, arguing that occupational injuries from electric shock and arc flash events, are well known in the health and safety world, but do not appear to have a high priority in the neurological field 43 This reflects national studies in Europe and Switzerland, which recognised that some occupations had a substantially higher risk of electric shocks than others.…”
Section: The Micro: Multiple System Atrophy (Msa)mentioning
confidence: 99%
See 2 more Smart Citations